1995
DOI: 10.1093/heapol/10.4.384
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of infant and child mortality in Tanzania

Abstract: This paper investigates the determinants of infant and child mortality in Tanzania using the 1991/92 Tanzania Demographic and Health Survey. A hazards model is used to assess the relative effect of the variables hypothesized to influence under-five mortality. Short birth intervals, teenage pregnancies and previous child deaths are associated with increased risk of death. The Government of the United Republic of Tanzania should therefore maintain its commitment to encouraging women to space their births at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
2
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 0 publications
9
56
2
1
Order By: Relevance
“…The first 28 days of extensive care for a new-born is of paramount importance, most of the neonatal deaths occurred in this period of which over 70% of neonatal deaths occur in the first six days of birth [7,8]. A study carried out by Singh et al [9] also showed lack of substantial evidence on the effectiveness of the content, frequency and timing of visits in standard ANC programs in maternal and child health.…”
Section: Survey Of Literaturementioning
confidence: 99%
“…The first 28 days of extensive care for a new-born is of paramount importance, most of the neonatal deaths occurred in this period of which over 70% of neonatal deaths occur in the first six days of birth [7,8]. A study carried out by Singh et al [9] also showed lack of substantial evidence on the effectiveness of the content, frequency and timing of visits in standard ANC programs in maternal and child health.…”
Section: Survey Of Literaturementioning
confidence: 99%
“…The GPR model allows flexibility in dealing with over-dispersion or under-dispersion [3]. More specifically, an NBR model is suggestive for dealing with over-dispersion [15].…”
Section: Statistical Modeling Of the Number Of Deaths Of Children In mentioning
confidence: 99%
“…However, in the presence of over-dispersion, Poisson regression model does not perform well in best fitting the data and for prediction. In this study, we test over-dispersion, [15,16] where the null hypothesis is that there is no overdispersion in the data. Hence, the Poisson regression model is the null model against any other alternative model with overdispersion.…”
Section: Model Justificationmentioning
confidence: 99%
See 2 more Smart Citations